A secularização e a fé : diálogo entre José Casanova e Joseph Ratzinger numa perspectiva teológico-pastoral - Wandscher, Aodomar José (2018)
The processes of secularization of the Western world have, in their wake, had several implications for the Christian faith. The present research proposes to make an analysis of the secularization and the faith in the current contemporaneity, in order to lay the foundations for a New Evangelization of the Church. For this, the work of the Spanish philosopher José Casanova, a sociologist of the religion, and the German Joseph Ratzinger, theologian and emeritus pope, is analyzed and put them into dialogue. Casanova's approach elucidates the phenomenon of secularization in its different facets, noting the emergence of public religions and the emergence of a globalized religious pluralism. Ratzinger's reflection (Benedict XVI) urges us to understand the faith as adherence to truth, in a context which he considers a "dictatorship of relativism". Although they are two very different paradigms, it is understood that this interdisciplinary relationship makes it possible to find elements to better understand the transmission of the faith in theological perspective